1971
DOI: 10.1149/1.2408230
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Wide, Flat Crystals of Silicon Web

Abstract: The temperature field and heat flow about the solidification interface of web crystals was modified by use of shaped radiation sinks. As a result, web was grown as wide as 3 cm and fiat to less than 2.5 ~m in 100 #m thick sheet. A qualitative extension of thermal models in dendrite growth applied to web morphology satisfactorily explains the experimentally observed results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

1975
1975
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 9 publications
2
9
0
1
Order By: Relevance
“…The dendrite tip contains 60 -corners and 120 -corners are observed at the edges the dendrite. This simulated appearance agrees well with the previous observation for Si or Ge [1,5,8]. We also investigate the side growth in the 〈111〉 direction perpendicular to the growth direction of the dendrite.…”
Section: Simulation Domain and Parameterssupporting
confidence: 90%
See 1 more Smart Citation
“…The dendrite tip contains 60 -corners and 120 -corners are observed at the edges the dendrite. This simulated appearance agrees well with the previous observation for Si or Ge [1,5,8]. We also investigate the side growth in the 〈111〉 direction perpendicular to the growth direction of the dendrite.…”
Section: Simulation Domain and Parameterssupporting
confidence: 90%
“…[16]. The F-model of the 〈112〉 dendrite suggests that the 〈112〉 dendrite becomes wider, but the width is almost constant in some experiments [8,18]. The Fmodel of the 〈110〉 dendrite seems to be more problematic.…”
Section: Introductionmentioning
confidence: 98%
“…Regarding the former, it is well known that the ͗112͘ dendrite is bounded by ͕111͖ planes and that it contains parallel twins. [8][9][10][11][12][13][14][15][16][17][18][19][20] To investigate the structural features of the ͗110͘ dendrite, we analyzed its crystallographic orientation ͑Fig. 4͒.…”
Section: Methodsmentioning
confidence: 99%
“…It was also shown that the preferential growth directions of Si faceted dendrites are ͗112͘ and ͗110͘. 18 Such features of faceted dendrites can be applied in technologies for growing thin Si ribbon crystals 13,14 and polycrystalline Si ingots 21,22 for solar cells. A growth mechanism for the dendrite preferentially grown along the ͗112͘ direction, hereafter referred to as a ͗112͘ dendrite, was first proposed in 1960.…”
Section: Introductionmentioning
confidence: 99%
“…11, where the cost of silicon sheet material is plotted vs ribbon width [18]. It should be noted that increasing the ribbon width from 25 to 50 mm reduces the sheet material cost from $678 to $3901m 2 • This cost projection is based on existing technology: 25-mm ribbon width, 1.5 m/h growth rate, $65/kg polycrystalline silicon cost, 0.3-mm ribbon thickness, and an eight percent ribbon solar cell efficiency.…”
Section: • Economic Outlookmentioning
confidence: 99%